Mutations in Hedgehog pathway genes in fetal rhabdomyomas. Issue 1 (6th August 2013) - Hettmer, Simone; Teot, Lisa A; van Hummelen, Paul; MacConaill, Laura; Bronson, Roderick T; Dall'Osso, Claudia; Mao, Junhao; McMahon, Andrew P; Gruber, Peter J; Grier, Holcombe E; Rodriguez‐Galindo, Carlos; Fletcher, Christopher D; et al.
Abstract: Ligand‐independent, constitutive activation of Hedgehog signalling in mice expressing a mutant, activated SmoM2 allele results in the development of multifocal, highly differentiated tumours that express myogenic markers (including desmin, actin, MyoD and myogenin). The histopathology of these tumours, commonly classified as rhabdomyosarcomas, more closely resembles human fetal rhabdomyoma (FRM), a benign tumour that can be difficult to distinguish from highly differentiated rhabdomyosarcomas. We evaluated the spectrum of Hedgehog (HH) pathway gene mutations in a cohort of human FRM tumours by targeted Illumina sequencing and fluorescence in situ hybridization testing for PTCH1 . Our studies identified functionally relevant aberrations at the PTCH1 locus in three of five FRM tumours surveyed, including a PTCH1 frameshift mutation in one tumour and homozygous deletions of PTCH1 in two tumours. These data suggest that activated Hedgehog signalling contributes to the biology of human FRM. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.